A Optimizing Raw Material Procurement EOQ Approach for Reducing Overstock: Mengoptimalkan Pengadaan Bahan Baku dengan Pendekatan EOQ untuk Mengurangi Persediaan yang Berlebih - Vidiasari, Mike; Jakaria, Ribangun Bamban (Universitas Muhammadiyah Sidoarjo, 2024)
This research employs the Economic Order Quantity (EOQ) method to optimize procurement practices for welding wire in boiler manufacturing. With a focus on reducing storage and inventory costs, the study aims to determine the optimal order quantity. Findings reveal that the calculated total inventory cost using the EOQ method significantly reduces compared to the company's existing policy. The optimal order quantity of 407 boxes, purchased four times per year, coupled with a safety stock of 181 boxes, ensures efficient procurement management. This research underscores the importance of implementing quantitative analysis techniques in procurement strategies to enhance cost-effectiveness and operational efficiency in manufacturing industries. Highlight : The study determines the optimal order quantity of K71T welding wire, reducing storage and inventory costs. The Economic Order Quantity (EOQ) method is applied, resulting in a total inventory cost of Rp. 89,060,000,- compared to the company policy of Rp. 290,840,000,-. The findings can be used as a reference for other manufacturing companies facing similar procurement challenges to optimize their inventory management and reduce costs. Keywords: welding wire, optimal order quantity, inventory management, procurement challenges, manufacturing companies